Study on urolithiasis diagnosed in a private medical centre in Rajshahi City (TAJ: Journal of Teachers Association, 2018)
It was a cross-sectional descriptive study. Sample size was 12227 of which 4148 were male and 8079 were female. Data were collected from all the patients attending the private medical centre, selected purposively, to have ultrasound examination for different reasons, during the calendar year 2016. A semi-structured questionnaire was used as the instrument of the study. It was observed that 18.32/1000 males and 9.90/1000 females had been diagnosed as cases of urolithiasis. Overall occurrence was calculated as 1.27%. Majority of the females had urolithiasis in the age-group of ‘up to 20 years’ (70%). In case of males, the problem was more common in ‘41 to 60 years’ and ‘61 years and above’ age-groups (62.5% and 66.7% respectively). Majority of the respondents had single stone only (68.6%). Kidney was the commonest site for the localization of both single (85.9%) and multiple stones (97.2%).TAJ 2016; 29(1): 24-28